DIGITAL LITERACY LEVEL AND TECHNOLOGY PERCEPTION OF ELEMENTARY SCHOOL TEACHER CANDIDATES' - Iscioglu, Ersun; Kocakusak, Suha (Hacettepe Univ, 2012)
Together with the developments in Information Technologies, digital data substituted traditional skills in all fields of our daily life. The information being transmitted in writing in traditional environment have started to be transmitted, archived and shared through images, vocal and motional displays as a result of these developments. Now it is very important for the teacher candidates to read, utilize digital technology and to adapt in novelties and to create designs with digital data and to have necessary skill and behavior to transfer them to their students so that integration of information technologies in social layers be achieved and to maintain the sustainability of this integration. In this study, the objective is to determine the digital literacy level and technology perception of elementary school teacher candidates'. This study is carried out through descriptive survey method. In this study, data is collected through Identification scale for digital literacy level of teacher candidates' developed by Kiyici (2008) and with utilizing focus group discussion method. Study group of this study is constituted of the Elementary School Teacher Education Program students of East Mediterranean University during 2011-2012 Spring Semester. Although the digital literacy level of teacher candidates has been determined to be high as a result of this study, it is also determined that their perception to use this technology both in their lecture of field and in their future teaching life is not so high.
Keywords: Digital Literacy; Technology Perception; Teacher Candidates